ChemInform Abstract: Water‐Dispersed Magnetic Nanoparticles (H2O‐DMNPs) of γ‐Fe2O3 for Multicomponent Coupling Reactions: A Green, Single‐Pot Technique for the Synthesis of Tetrahydro‐4H‐chromenes and Hexahydroquinoline Carboxylates. Issue 41 (19th September 2013) - Rostamnia, Sadegh; Nuri, Ayat; Xin, Hongchuan; Pourjavadi, Ali; Hosseini, Seyed Hassan
Abstract Knoevenagel—Michael cyclization reactions under the optimized conditions afford the heterocycles with excellent yields.